Regulatory Diversity and Functional Analysis of Two-Component Systems in Cyanobacterium Synechocystis sp. PCC 6803 by GC-MS Based Metabolomics - Shi, Mengliang; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2020)
Two-component signal transduction systems are still poorly functionally characterized in model cyanobacterium Synechocystis sp. PCC 6803. To address the issue, a GC-MS based metabolomic analysis was conducted on a library of 44 knockout mutants for the response regulators (RRs) in Synechocystis. The metabolomic profiling analysis showed that 7 RRs mutants, namely Δslr1909, Δsll1291, Δslr6040, Δsll1330, Δslr2024, Δslr1584 and Δslr1693, were significantly different at metabolomic level, although their growth patterns are similar to the wild type under the normal autotropic growth condition, suggesting of regulatory diversity of RRs at metabolite level. Additionally, a detailed metabolomic analysis coupled with RT-qPCR verification led to useful clues for possible functions of these 7 RRs, which were involved in the regulation of multiple aspects of cellular metabolisms in Synechocystis. Moreover, an integrative metabolomic and evolutionary analysis of all RR showed that 4 groups of RR genes were clustered together in both metabolomic and evolutionary trees, suggesting of possible functional conservation of these RRs during the evolution. Meanwhile, 6 groups of RRs with close evolutionary origins were found with different metabolomic profiles, suggesting possible functional changes during evolution. In contrast, more than 10 groups of RR genes with different clustering patterns in the phylogenetic tree were found clustered together in a metabolomics-based tree, suggesting possible functional convergences during the evolution. The study provided a metabolomic view of RR function, and the most needed functional clues for further characterization of these regulatory proteins in Synechocystis.